Letter from Georg Bredig to Max Bredig, August 6, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) provides feedback on an offer that his son, Max Bredig (1902-1977), has received to work in Sweden with the Swedish chemist, Olof Arrhenius (1895-1977). Olof Arrhenius was the oldest son of Svante Arrhenius (1859-1917), a renowned physicist, chemist, and winner of the Nobel Prize for Chemistry in 1903.
Keywords: Third Reich